Impact of pre-transplant anti-MICA sensitization in graft rejection and survival - Costa, R. (2015)
Background: Evidence supporting deleterious effect of preformed major histocompatibility class I chain-related A (MICA) antibodies in rejection incidence and graft survival is still unclear. Methods: Retrospective analysis of 554 kidney transplanted patients. Comparison between positive or negative for MICA antibodies patients was performed to characterize sensitizing triggers. Further classification according to pre-transplant flow cytometry-recorded anti–MICA and/or anti-human leukocyte antigen (HLA) antibodies was made to determine first year rejection incidence and graft survival. Multivariate analysis was applied to determine predictors for acute rejection. Results: Pre-formed anti-MICA antibodies were detected in 41 patients (7.4%). HLA sensitization, blood transfusions and pregnancies were frequently found in anti-MICA+ patients but only pre-formed anti-HLA class I antibodies showed independent association (OR 2.67, p= 0.02). Comparing to MICA-/HLA–, MICA-/HLA+ group presented significantly lower first year rejection-free survival (78.6% vs. 89.3%, p< 0.01), mostly occurred in the first six months, while no difference was found in MICA+/HLA– (88.9% vs. 89.3%, p= ns). MICA-/HLA+ showed independent impact in rejection (OR 2.09, p= 0.03), while no evidence was found in MICA+/HLA- (OR 1.08, p= ns). At 4 years, MICA-/HLA+ group presented lower graft survival (85.8% vs. 95.3%, p= 0.03). Again, no difference was found in MICA+/HLA- group (95.1% vs. 95.3%, p= ns). Conclusion: Our results do not support HLA-independent deleterious pathogenic role of pre-formed MICA antibodies on first year rejection incidence and graft survival.